PERANCANGAN SISTEM INFORMASI SIMPAN PINJAM DI KOPERASI BINA MASYARAKAT TARATAK KOTO LUA KECAMATAN PAUH PADANG BERBASIS JAVA - Elmawati Elmawati (Jurnal Teknologi Informasi dan Pendidikan, 2018)
The Designation of Save Loan Information System in Cooperative Community Development Koto Lua District Pauh Padang database to be more easier in processing save-loan cooperation data. This system can process member data, saving and loan. Then, in data processing it can process faster than usual so it is raised a report and information of save-loan cooperation that are suitable with members. Necessity data processing is done by the administration Cooperative Community Development Koto Lua District Pauh Padang agreed by leader and treasurer